A perspective of mitochondrial dysfunction in rats treated with silver and titanium nanoparticles (AgNPs and TiNPs) - Pereira, Lilian Cristina [UNESP]; Pazin, Murilo; Franco-Bernardes, Mariana Furio; Martins, Airton da Cunha; Barcelos, Gustavo Rafael Mazzaron; Pereira, Márcio Cesar; Mesquita, João Paulo; Rodrigues, Jairo Lisboa; Barbosa, Fernando; Dorta, Daniel Junqueira [UNESP] (Elsevier, 2018)
Nanotechnology is a growing branch of science that deals with the development of structural features bearing at least one dimension in the nano range. More specifically, nanomaterials are defined as objects with dimensions that range from 1 to 100 nm, which give rise to interesting properties. In particular, silver and titanium nanoparticles (AgNPs and TiNPs, respectively) are known for their biological and biomedical properties and are often used in consumer products such as cosmetics, food additives, kitchen utensils, and toys. This situation has increased environmental and occupational exposure to AgNPs and TiNPs, which has placed demand for the risk assessment of NPs. Indeed, the same properties that make nanomaterials so attractive could also prove deleterious to biological systems. Of particular concern is the effect of NPs on mitochondria because these organelles play an essential role in cellular homeostasis. In this scenario, this work aimed to study how AgNPs and TiNPs interact with the mitochondrial respiration chain and to analyze how this interaction interferes in the bioenergetics and oxidative state of the organelles after sub-chronic exposure. Mitochondria were exposed to the NPs by gavage treatment for 21 days to check whether co-exposure of the organelles to the two types of NPs elicited any mitochondrion-NP interaction. More specifically, male Wistar rats were randomly assigned to four groups. Groups I, II, III, and IV received mineral oil, TiNPs (100 μg/kg/day), AgNPs (100 μg/kg/day), and TiNPs + AgNPs (100 μg/kg/day), respectively, by gavage. The liver was immediately removed, and the mitochondria were isolated and used within 3 h. Exposure of mitochondria to TiNPs + AgNPs lowered the respiratory control ratio, causing an uncoupling effect in the oxidative phosphorylation system. Moreover, both types of NPs induced mitochondrial swelling. Extended exposure of mitochondria to the NPs maintained increased ROS levels and depleted the endogenous antioxidant system. The AgNPs and TiNPs acted synergistically—the intensity of the toxic effect on the mitochondrial redox state was more significant in the presence of both types of NPs. These findings imply that the action of the NPs on mitochondria underlie NP toxicity, so future application of NPs requires special attention.
Keywords: Mitotoxicants; Nanomaterials; Silver nanoparticles; Titanium nanoparticles